The Politics of Violence in Latin America - Policzer, Pablo (Latin American & Caribbean Studies, 2019)
A reexamination of the causes of violence in Latin America and a challenge to preconceptions of the possibility of change. Latin America is one of the most violent regions in the world. It has suffered waves of repressive authoritarian rule, organized armed insurgency and civil war, violent protest, and ballooning rates of criminal violence. But is violence hard-wired into Latin America? This is a critical reassessment of the ways in which violence in Latin America is addressed and understood. Previous approaches have relied on structural perspectives, attributing the problem of violence to Latin America's colonial past or its conflictual contemporary politics. Bringing together scholars and practitioners, this volume argues that violence is often rooted more in contingent outcomes than in deeply embedded structures. Addressing topics ranging from the root sources of violence in Haiti to kidnapping in Colombia, from the role of property rights in patterns of violence to the challenges of peacebuilding, The Politics of Violence in Latin America is an essential step towards understanding the causes and contexts of violence-and changing the mechanisms that produce it.